Designing an electronic program to evaluate the grades of the objective examinations according to the time and its relation to the accuracy of the answers of the students of the technical institute / Shatrah in Iraq - Suhad Abbas Yasser, (Journal of engineering sciences and information technology, 2018)
The study aimed to design an electronic program to evaluate the grades of the objective examinations according to time and their relation to the accuracy of the answer. The researcher used the experimental method. To achieve the goal of the study، the researcher designed an electronic program to evaluate the students' grades. The program consists of the inputs and the content of the program in addition to its outputs in giving the objective evaluation. And the proposed design for the development of the evaluation of the university students electronically، was applied to a sample of 30 students from the Technical Institute / Shatrah in Iraq. The results showed that the electronic evaluation (4.00 / 4.93 / 5.93) for the normal group while the mean of the experimental group (6،10 / 6،04 / 500) was high compared to the normal evaluation. There are significant differences at the level The significance (α = 0.05) was due to a variable favorability for females in the decision to complete the study in an electronic university، and in view of the results، a number of recommendations and proposals were presented to enhance the experiment and organize the benefit from it